Leukemia inhibitory factor enhances the development and subsequent blastocysts quality of yak oocytes in vitro - Zhao, Tian; Pan, Yangyang; Li, Qin; Ding, Tianyi; Niayale, Robert; Zhang, Tongxiang; Wang, Jinglei; Wang, Yaying; Zhao, Ling; Han, Xiaohong; Baloch, Abdul Rasheed; Cui, Yan; et al. (Frontiers in Veterinary Science, 2022)
Leukemia inhibitory factor (LIF) is a multipotent cytokine of the IL-6 family which plays a critical role in the maturation and development of oocytes. This study evaluated the influence of LIF on the maturation and development ability of yak oocytes, and the quality of subsequent blastocysts under in vitro culture settings. Different concentrations of LIF (0 ng/mL, 25 ng/mL, 50 ng/mL, 100 ng/mL) were added during the in vitro culture of oocytes to detect the maturation rate of oocytes, levels of mitochondria, reactive oxygen species (ROS), actin, and apoptosis in oocytes, mRNA transcription levels of apoptosis and antioxidant-related genes in oocytes, and total cell number and apoptosis levels in subsequent blastocysts. The findings revealed that 50 ng/mL LIF could significantly increase the maturation rate (p < 0.01), levels of mitochondria (p < 0.01) and actin (p < 0.01), and mRNA transcription levels of anti-apoptotic and antioxidant-related genes in yak oocytes. Also, 50 ng/mL LIF could significantly lower the generation of ROS (p < 0.01) and apoptosis levels of oocytes (p < 0.01). In addition, blastocysts formed from 50 ng/mL LIF-treated oocytes showed significantly larger total cell numbers (p < 0.01) and lower apoptosis rates (p < 0.01) than the control group. In conclusion, the addition of LIF during the in vitro maturation of yak oocytes improved the quality and the competence of maturation and development in oocytes, as well as the quality of subsequent blastocysts. The result of this study provided some insights into the role and function of LIF in vitro yak oocytes maturation, as well as provided fundamental knowledge for assisted reproductive technologies in the yak.